SST2 as a novel biomarker for the prediction of in-hospital mortality after coronary artery bypass grafting. (3rd April 2019) - Stabler, Meagan E.; Rezaee, Michael E.; Parker, Devin M.; MacKenzie, Todd A.; Bohm, Andrew R.; DiScipio, Anthony W.; Malenka, David J.; Brown, Jeremiah R.
Abstract: Objectives : Soluble suppression of tumorigenicity 2 (sST2) biomarker is an emerging predictor of adverse clinical outcomes, but its prognostic value for in-hospital mortality after coronary artery bypass grafting (CABG) is not well understood. This study measured the association between operative sST2 levels and in-hospital mortality after CABG. Methods : A prospective cohort of 1560 CABG patients were analyzed from the Northern New England Cardiovascular Disease Study Group Biomarker Study. The primary outcome was in-hospital mortality after CABG surgery ( n  = 32). Results : After risk adjustment, patients in the third tercile of pre-, post- and pre-to-postoperative sST2 values experienced significantly greater odds of in-hospital death compared to patients in the first tercile of sST2 values. The addition of both postoperative and pre-to-postoperative sST2 biomarker significantly improved ability to predict in-hospital mortality status following CABG surgery, compared to using the EuroSCORE II mortality model alone, (c-statistic: 0.83 [95% CI: 0.75, 0.92], p value 0.0213) and (c-statistic: 0.83 [95% CI: 0.75, 0.92], p value 0.0215), respectively. Conclusion : sST2 values are associated with in-hospital mortality after CABG surgery and postoperative and pre-to-post operative sST2 values improve prediction. Our findings suggest that sST2 can be used as a biomarker to identify adult patients at greatest risk of in-hospital death after CABG surgery.